E-Learning Development Based on Multimedia Learning Strategies to Improve Learning Outcomes - Kusmayadi Kusmayadi; Nurdin Ibrahim; Sigit Wibowo (Journal of Educational Sciences, 2026)
Limited instructional time and the lack of interactive learning media have contributed to low Physics learning outcomes, particularly in understanding abstract concepts. These conditions indicate the need for an effective digital learning solution that integrates structured instructional strategies and multimedia support. This study aims to develop and evaluate a multimedia-based e-learning model using the LEARN (Listen, Explore, Apply, Reflect, and Navigate) learning strategy to improve the Physics learning outcomes of 10th-grade students. The research employed a Research and Development (R&D) approach by integrating the Borg and Gall model with the Lee and Owens framework. Data were collected through interviews, questionnaires, expert validation instruments, and learning outcome tests. The developed e-learning model was validated by material, media, and instructional design experts and tested through one-to-one, small-group, and large-group trials. The effectiveness of the model was examined using a quasi-experimental design with experimental and control groups. The results indicate that the multimedia-based e-learning model is highly feasible and leads to higher learning gains compared to conventional learning modules. In conclusion, multimedia-based e-learning can effectively enhance Physics learning outcomes in learning environments with limited face-to-face instructional time.